Macroscopic assembly style of catalysts significantly determining their efficiency for converting CO2 to gasoline. Issue 19 (10th September 2019) - Wang, Xiaoxing; Yang, Guohui; Zhang, Junfeng; Song, Faen; Wu, Yingquan; Zhang, Tao; Zhang, Qingde; Tsubaki, Noritatsu; Tan, Yisheng
Abstract : Efficient conversion of CO2 into high-quality gasoline is realized over a Fe–Zn–Zr and HZSM-5 core–shell catalyst. Abstract : Although considerable efforts have been made in converting CO2 via hydrogenation to gasoline, the selectivity to high-quality gasoline with high C5+ isoalkane and low aromatics amounts remains a challenge. Here, the efficient conversion of CO2 into gasoline is realized over a bifunctional Fe–Zn–Zr and HZSM-5 catalyst with a core–shell assembly style. The selectivity for gasoline (C5+ hydrocarbon) reaches 55.8% in total hydrocarbons, with 91.9% C5+ isoalkanes and only 5.2% aromatics in gasoline at 21.5% CO2 conversion. It is demonstrated that the predominant performance of the bifunctional Fe–Zn–Zr@HZSM-5 catalyst depends strongly on the appropriate Brønsted acid sites and shell thickness of the zeolite as well as the core–shell structure. The good match of the acidity and shell thickness of the zeolite in the core–shell catalyst is vital for suppressing the undesired deep hydrogenation and aromatization reactions. Meanwhile, the core–shell structure not only favors the formation of gasoline and C5+ isoalkanes by controlling the consecutive secondary reactions, but also boosts the conversion of the oxygen compounds via the abundant interfaces of the two active components. Moreover, the Fe–Zn–Zr@HZSM-5 catalyst exhibits an extremely good stability for 100 h, providing a promising route for CO2 utilization to obtain high-quality gasoline.